2014
DOI: 10.1002/ijc.29215
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide CNV analysis in 221 unrelated patients and targeted high‐throughput sequencing reveal novel causative candidate genes for colorectal adenomatous polyposis

Abstract: To uncover novel causative genes in patients with unexplained adenomatous polyposis, a model disease for colorectal cancer, we performed a genome-wide analysis of germline copy number variants (CNV) in a large, well characterized APC and MUTYH mutation negative patient cohort followed by a targeted next generation sequencing (NGS) approach. Genomic DNA from 221 unrelated German patients was genotyped on high-resolution SNP arrays. Putative CNVs were filtered according to stringent criteria, compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 50 publications
2
61
1
Order By: Relevance
“…9 In addition, a single nucleotide polymorphism (SNP) array-based CNV analysis was performed in all individuals, as described elsewhere. 28 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In addition, a single nucleotide polymorphism (SNP) array-based CNV analysis was performed in all individuals, as described elsewhere. 28 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, all genes carrying the remaining rare variants were inspected for the presence of rare, non-polymorphic heterozygous CNVs of ≥ 10 kb in order to identify additional recurrently mutated genes or biallelic, compound-heterozygous variants. 28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 DNA CNVs include gene amplification, gain, loss and deletion. In addition to gene mutation, CNV has a significant role in tumorigenesis in many cancers, such as GC, 13 ovarian cancer, 14 hepatocellular carcinoma, 15 testicular germ cell tumors, 16 colorectal carcinoma, 17 bladder cancer 18 and so on. The accumulation of CNVs during gastric oncogenesis may be a result of preferential selection by which transforming cells gain evolutionary advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study identified germline mutation in SMARCA4 , another member of the SNF/SW1 superfamily, in several polyposis families,17 suggesting that members of chromatin remodellers are important regulators of tumourigenesis process. We investigated the expression of the H1 binding domain of CHD8 ( CHD8H1 ) in a subset of cases but found that the expression did not follow their CN status in both mucosa and tumours normalised to their matched mucosa.…”
Section: Discussionmentioning
confidence: 99%